Efficacy of wearable technology at quantifying power and total work of endurance runners against varying wind resistance - Bello, M.; Williamson, P.; Price, F.; Shepherd, B.; Smith, J. (The Journal of Strength and Conditioning Research, 2021)
Wearable technology has increased in popularity due to live feedback allowing training session adjustment in real time. In addition to HR monitoring, measuring power and total work may supplement other performance metrics and demonstrate differences in physical measures for training sessions with similar physiological stress. Purpose: The purpose of this study was to examine the efficacy of wearable technology at determining power and total work of endurance runners while running against varying levels of wind resistance. Methods: Eight trained endurance runners (5 females, 3 males) were recruited for this study and were currently running at least 120 min/wk for the past 3 months. Subjects completed 3 sessions: 1 preliminary and 2 testing. All sessions were performed at least 2 hours fasted, at the same time of day, and subjects were asked to follow the same dietary intake prior to each session. Preliminary testing included screening and a VO2peak protocol. Subjects then completed 2 testing sessions in randomized order: one with no wind resistance (W0), and one with a wind resistance of 10 mph (W10). Each session involved a 20-minute run at 70% VO2peak. Power and total work were calculated using a power meter, HR was monitored via HR monitor, and RER, VO2 were monitored using a metabolic cart. The middle 10 minutes were analyzed for session means to avoid non steady state measures associated with beginning exercise and anticipation of completion. Paired t-tests were used to compare differences between sessions for all variables. Significance was set at p < 0.05. Results: There were no significant differences between RER, HR, or VO2 (p > 0.294) between sessions. There was a significant difference for power, with higher values in W10 compared to W0 (378.2 ± 45.2 vs. 364.5 ± 43.9 W; p = 0.001) There was also a significant difference for total work, with a higher work output in W10 compared to W0 (226.9 ± 27.1 vs. 218.7 ± 26.3 kJ; p = 0.001). Conclusions: The lack of significance in RER, HR, and VO2 demonstrates these runners sustained a similar physiological response for both testing sessions. However, the addition of wind resistance caused a significant increase in power and work output assessed by wearable technology in these endurance runners. These data indicate differences in physical performance in combination with the similar physiological response reflects the efficacy in the power meter for quantifying power and total work. Practical Applications: The use of a power meter to provide live feedback during training may be beneficial in assessing overall training stress. The differences seen in power and total work between testing sessions indicates the potential of the technology to assess physical changes. Further, the accumulation of differences in workload over time may result in a more robust physiological response. Therefore, the use of a power meter should be used in conjunction with HR monitoring.